Composite solid electrolyte taking chromium carbide as filler and preparation method of composite solid electrolyte
By introducing chromium carbide filler into the solid electrolyte and blending it with polyethylene oxide and combining specific additives, the problems of low conductivity and narrow electrochemical window of the solid electrolyte are solved, and efficient ion conduction and cell stability are achieved.
Patent Information
- Application Number
- CN202411941256.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
The ionic conductivity of pure polyethylene oxide solid electrolytes is relatively low under room temperature conditions, and the electrochemical window is relatively narrow, limiting the battery's energy transfer efficiency and response speed.
Using chromium carbide as filler, composite solid electrolytes are prepared by blending with polyethylene oxide and adding specific additives (such as succinitrile and lithium bistrifluoromethanesulfonimide). This method synthesizes chromium carbide by carbonization and improves conductivity through metal bonds, covalent bonds and ionic bonds.
The ionic conductivity and electrochemical window of the composite solid electrolyte are significantly improved, and the high stability and cycling performance of lithium metal batteries are achieved.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy storage material development, and relates to a composite solid electrolyte using chromium carbide as filler and a preparation method thereof. Background Art
[0002] Solid-state electrolytes are gradually becoming a strong candidate to replace traditional commercial liquid electrolytes in lithium metal batteries due to their excellent safety and output power stability in energy storage devices. This transformation not only heralds the innovation of battery technology, but also places the industry's expectations for higher performance and more reliable battery systems. However, pure polyethylene oxide-based solid electrolytes have encountered several key challenges in practical applications, the most prominent of which is its low ionic conductivity at room temperature, which directly limits the energy transfer efficiency and response speed of the battery. In addition, this type of electrolyte also faces the problem of weak ion transfer number, which is related to the smoothness of charge migration inside the battery, which in turn affects the overall performance of the battery. What's more troublesome is that its electrochemical window is relatively narrow, which means that within a specific voltage range, the electrolyte may not work stably, increasing the risk of battery failure.
[0003] In order to overcome these bottlenecks, researchers have been exploring a variety of improvement strategies, one of which is to introduce inorganic fillers such as oxides and sulfides into polymer solid electrolytes. The original intention of adding these fillers was to improve the ion conductivity of the electrolyte by changing its structure and properties. However, although this method has reduced the stability problem of the polymer to a certain extent, the effect of improving ionic conductivity has not met the ideal expectations, and it is still difficult to meet the needs of high-performance battery applications. Therefore, how to effectively improve the ionic conductivity and broaden the electrochemical window while maintaining the safety and stability advantages of solid electrolytes is still a hot topic and difficulty in current research. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a composite solid electrolyte with chromium carbide as filler and a preparation method thereof, thereby solving the technical problems of low conductivity and narrow chemical window of pure polyethylene oxide-based solid electrolytes in the prior art.
[0005] The present invention is achieved through the following technical solutions: A method for preparing a composite solid electrolyte using chromium carbide as filler comprises the following steps: S1: adding glucose to chromium nitrate solution, stirring and mixing, and drying to obtain mixture A; mixing mixture A with carbon black, grinding, adding isopropanol, ball milling, and drying to obtain mixture B; S2: Carburizing the mixture B under a nitrogen atmosphere to obtain chromium carbide; S3: Blending the chromium carbide with polyethylene oxide, adding them to N,N'-dimethylformamide, heating and stirring, then adding succinonitrile and lithium bis(trifluoromethanesulfonyl imide), continuing heating and stirring to completely dissolve the mixture, and mixing evenly, and after drying, obtaining the composite solid electrolyte with chromium carbide as filler.
[0006] Preferably, the ratio of glucose to chromium nitrate is 3:(5-15) by mass.
[0007] Preferably, in terms of mass fractions, the ratio of the mixture A to carbon black is (1-3):5.
[0008] Preferably, the mixture A is mixed with carbon black and then ground, and isopropanol is added. During ball milling, the rotation speed is 400-600 rpm and the ball milling time is 6-12 h.
[0009] Preferably, in step S2, the carbonization process is specifically as follows: controlling the heating rate to be 5-10°C min -1 , heat to 1100~1400℃, keep warm for 1~5 h, and control the cooling rate to 1~5℃ min -1 , to room temperature, completing the carbonization process.
[0010] Preferably, the ratio of the chromium carbide to the polyethylene oxide is (2-8):(8-12) in parts by mass.
[0011] Preferably, the ratio of succinonitrile to lithium bis(trifluoromethanesulfonyl)imide is (10-50):1 in parts by mass.
[0012] Preferably, in step S3, after adding succinonitrile and lithium bis(trifluoromethanesulfonyl imide), heating and stirring are continued at a temperature of 50-80° C. for 10-16 h.
[0013] A composite solid electrolyte with chromium carbide as filler is prepared by the above method; the ionic conductivity of the composite solid electrolyte with chromium carbide as filler at room temperature is 1*10 -6 ~1*10 -4 S cm -1 , the electrochemical window is 3.5V~5.5V.
[0014] A lithium metal battery comprises the above-mentioned composite solid electrolyte with chromium carbide as filler.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a composite solid electrolyte with chromium carbide as filler. In the method, chromium carbide is firstly synthesized by a simple ball milling carbonization process. Chromium carbide is a polar compound with high bonding ability and excellent electrical conductivity. Chromium carbide can be combined with polyethylene oxide through metal bonds, covalent bonds and ionic bonds, thereby inhibiting ion pairing between anions and lithium ions, so that more free lithium ions are transmitted back and forth between positive and negative electrodes, thereby improving the electrical conductivity of the composite solid electrolyte. At the same time, chromium carbide interacts with lithium salt anions through coordination bonds, inhibiting their movement, thereby allowing more lithium ions to be transported back and forth between the positive and negative electrodes, thereby improving the electrical conductivity of the composite solid electrolyte. The invention relates to a method for preparing a lithium metal battery having a plurality of chromium carbide films and a plurality of chromium carbides. The invention relates to a method for preparing a lithium metal battery having a plurality of chromium carbides ...
[0016] Furthermore, the ratio of glucose to chromium nitrate is 3:(5-15) by mass, which can ensure that the target product chromium carbide is obtained.
[0017] Furthermore, the ratio of the mixture A to the carbon black is (1-3):5 in terms of mass fraction, which can ensure sufficient carbon source to prepare the target product chromium carbide.
[0018] Furthermore, the mixture A is mixed with carbon black and then ground, and isopropanol is added. During ball milling, the rotation speed is 400-600 rpm and the ball milling time is 6-12 h, so that the mixture can be fully mixed.
[0019] Furthermore, in step S2, the carbonization process is specifically as follows: the heating rate is controlled to be 5-10°C min -1 , heat to 1100~1400℃, keep warm for 1~5 h, and control the cooling rate to 1~5℃ min -1 , and then cool to room temperature to complete the carbonization process, so as to obtain the target product chromium carbide.
[0020] Furthermore, the ratio of chromium carbide to polyethylene oxide is (2-8):(8-12) by weight, which can ensure that a product with excellent performance is obtained.
[0021] Furthermore, the mass ratio of polyethylene oxide to lithium bis(trifluoromethanesulfonyl)imide is (16-1):(18-1), which can achieve a good film-forming effect.
[0022] Furthermore, in step S3, after adding succinonitrile and lithium bis(trifluoromethanesulfonyl)imide, heating and stirring are continued at a temperature of 50-80° C. for 10-16 h to allow the substances to be fully mixed and dissolved. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 XRD spectra of the composite solid electrolytes prepared in Examples 1 to 3 of the present invention; Figure 2 The electrochemical window diagram of the composite solid electrolyte prepared in Examples 1 to 3 of the present invention; Figure 3 The electrochemical impedance spectra (a) of the composite solid electrolytes prepared in Examples 1 to 3 of the present invention at 25° C. and the ionic conductivities (b) at different temperatures. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0027] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0030] The present invention provides a method for preparing a composite solid electrolyte using chromium carbide as filler, comprising the following steps: S1: adding glucose to chromium nitrate solution, stirring and mixing, and drying to obtain mixture A; mixing mixture A with carbon black, grinding, adding isopropanol, ball milling, and drying to obtain mixture B; Wherein, in terms of mass fractions, the ratio of glucose to chromium nitrate is 3:(5-15). The ratio of mixture A to carbon black is (1-3):5.
[0031] Mixture A and carbon black are mixed and ground, and isopropanol is added. During ball milling, the rotation speed is 400-600 rpm and the ball milling time is 6-12 h.
[0032] S2: Carburizing the mixture B under a nitrogen atmosphere to obtain chromium carbide; The carbonization process is as follows: the heating rate is controlled at 5~10℃ min -1 , heat to 1100~1400℃, keep warm for 1~5 h, and control the cooling rate to 1~5℃ min -1 , to room temperature, completing the carbonization process.
[0033] S3: Blending the chromium carbide with polyethylene oxide, adding them to N,N'-dimethylformamide, heating and stirring, then adding succinonitrile and lithium bis(trifluoromethanesulfonyl imide), continuing heating and stirring to completely dissolve the mixture, and mixing evenly, and after drying, obtaining the composite solid electrolyte with chromium carbide as filler.
[0034] In terms of mass fractions, the ratio of chromium carbide to polyethylene oxide is (2-8):(8-12). The mass ratio of succinonitrile to lithium bis(trifluoromethanesulfonyl)imide is (10-50):1.
[0035] After adding succinonitrile and lithium bis(trifluoromethanesulfonyl imide), heating and stirring are continued at a temperature of 50-80°C for a time of 10-16 h.
[0036] Preferably, the above process is: A method for preparing a composite solid electrolyte using chromium carbide as filler comprises the following steps: Step 1, according to the mass fraction, 3 parts of chromium nitrate are dissolved in 50 parts of distilled water, heated and stirred at 25-35°C until dissolved, 5-15 parts of glucose are added to ensure sufficient carbon source, heated and stirred at 25-35°C until completely dissolved. Then, the solution is placed in an oven to dry, the temperature is set to 60-100°C, and the drying time is 6-10 h to obtain the target product 1; Step 2, according to the mass fraction, the target product 1 and carbon black are mixed in a ratio of (1-3):5, and manually ground for 0.5-2 h. Then add an appropriate amount of isopropanol, use a ball mill for mechanical grinding, set the grinding ball mass to sample mass ratio (50-100):1, the rotation speed is 400-600 rpm, and the ball milling time is 6-12 h. After completion, dry in an oven for 3-8 h at a temperature of 50-100 ° C to obtain the target product 2; Step 3: According to the mass fraction, 3-8 parts of the target product 2 are placed in a tube furnace for high-temperature carbonization, and argon gas is introduced as a protective gas at a flow rate of 20-50 mL min -1 The reaction temperature is 1100~1400℃, and the heating rate is controlled at 5~10℃min -1 The cooling rate is controlled at 1~5℃ min -1 , the reaction time is 1~5 h. After the carbonization reaction is completed, the concentration is 0.1~0.5 mol L -1 After repeated rinsing with hydrochloric acid for 1 to 5 times, continue to use distilled water and anhydrous ethanol to repeat rinsing for 1 to 5 times. After completion, dry in an oven for 3 to 8 hours at a temperature of 50 to 100 ° C to obtain the target product 3; Step 4, according to the mass fractions, 2 to 8 parts of the target product 3 and 8 to 12 parts of polyethylene oxide are blended and added into a round-bottom flask containing 25.0 to 50.0 mL of N,N'-dimethylformamide, wherein the solid content is 3% to 8% (the solid content here refers to the mass percentage of the target product 3 in the polyethylene oxide), heated at 50 to 80°C, and stirred for 1 to 3 hours. Subsequently, succinonitrile and lithium bistrifluoromethanesulfonyl imide are added, wherein the ratio of succinonitrile to lithium bistrifluoromethanesulfonyl imide is (10-50):1 by weight, and the ratio of polyethylene oxide to lithium bistrifluoromethanesulfonyl imide is (16-20):1 by weight, so that excellent conductivity of the composite solid electrolyte can be obtained, and heating and stirring are continued for 10-16 hours to completely dissolve the mixture and mix it evenly. Finally, the above mixture is poured into a polytetrafluoroethylene plate and dried in a vacuum oven at 30-70°C for 24-48 hours to obtain a composite solid electrolyte.
[0037] The present invention also discloses a composite solid electrolyte with chromium carbide as filler prepared by the above method, wherein the ionic conductivity of the composite solid electrolyte with chromium carbide as filler at room temperature is 1*10 -6 ~1*10 -4 S cm -1 , the electrochemical window is 3.5V~5.5V.
[0038] The chromium carbide used in the present invention is a polar compound with high bonding strength, and the conductivity of the composite solid electrolyte can be improved by combining metal bonds, covalent bonds and ionic bonds; the -C≡N group of succinonitrile has high oxidation stability, physically isolates the direct contact between PEO and the high-voltage positive electrode, and inhibits the oxidative decomposition of PEO; the PEO matrix has the advantages of low cost, good flexibility and good processability, and has been widely studied. Finally, a composite solid electrolyte with conductive metal carbide as filler is constructed, which has excellent ionic conductivity, stable interface, wide electrochemical window and other characteristics, and realizes high stability and cycle performance of lithium metal batteries.
[0039] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0040] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0041] Example 1 Step 1, dissolve 1.65 g of chromium nitrate in 50 mL of distilled water, heat and stir at 30°C until dissolved, add 2.75 g of glucose to ensure sufficient carbon source, heat and stir at 30°C until completely dissolved. Then, place the solution in an oven to dry, set the temperature to 80°C, and dry for 8 h to obtain the target product 1; Step 2, weigh 0.75 g of product 1 and 2.35 g of carbon black, grind manually for 1 h. Then add an appropriate amount of isopropanol, use a ball mill for mechanical grinding, set the ratio of grinding ball mass to sample mass to 50:1, the rotation speed is 450 rpm, and the ball milling time is 8 h. After completion, dry in an oven for 5 h at 80 ° C to obtain the target product 2; Step 3: 0.5 g of the target product 2 was placed in a tube furnace for high-temperature carbonization, and argon was introduced as a protective gas at a flow rate of 40 mL min -1 The reaction temperature was 1400 °C and the heating rate was controlled at 10 °C min -1 The cooling rate is controlled at 3℃min -1 , the reaction time was 2 h. After the carbonization reaction was completed, the concentration was 0.1 mol L -1 After repeated rinsing with hydrochloric acid for 1-5 times, continue to use distilled water and anhydrous ethanol to repeat rinsing for 1-5 times. After completion, dry in an oven for 6 hours at a temperature of 80°C to obtain the target product 3; Step 4, 0.04 g of the target product 3 was mixed with 1.0 g of polyethylene oxide, added to a round-bottom flask containing 25.0 mL of N,N'-dimethylformamide, with a solid content of 4%, heated at 60 ° C, and stirred for 2.5 h. Then, 0.4 g of succinonitrile and 0.3 g of lithium bis(trifluoromethanesulfonylimide) (polyethylene oxide: lithium bis(trifluoromethanesulfonylimide) = 18:1) were added, and the mixture was heated and stirred at 65 ° C for 16 h to completely dissolve the mixture and mix it evenly. Finally, the above mixture was poured into a polytetrafluoroethylene plate and dried at 60 ° C in a vacuum oven for 48 h to obtain a composite solid electrolyte, recorded as PEOCCSN-4.
[0042] Example 2 Step 1, dissolve 1.65 g of chromium nitrate in 50 mL of distilled water, heat and stir at 30°C until dissolved, add 2.75 g of glucose to ensure sufficient carbon source, heat and stir at 30°C until completely dissolved. Then, place the solution in an oven to dry, set the temperature to 80°C, and dry for 8 h to obtain the target product 1; Step 2, weigh 0.75 g of product 1 and 2.35 g of carbon black, grind manually for 1 h. Then add an appropriate amount of isopropanol, use a ball mill for mechanical grinding, set the ratio of grinding ball mass to sample mass to 50:1, the rotation speed is 450 rpm, and the ball milling time is 8 h. After completion, dry in an oven for 5 h at 80 ° C to obtain the target product 2; Step 3: 0.5 g of the target product 2 was placed in a tube furnace for high-temperature carbonization, and argon was introduced as a protective gas at a flow rate of 40 mL min -1 The reaction temperature was 1400 °C and the heating rate was controlled at 10 °C min -1 The cooling rate is controlled at 3℃min -1 , the reaction time was 2 h. After the carbonization reaction was completed, the concentration was 0.1 mol L -1After repeated rinsing with hydrochloric acid for 1-5 times, continue to use distilled water and anhydrous ethanol to repeat rinsing for 1-5 times. After completion, dry in an oven for 6 hours at a temperature of 80°C to obtain the target product 3; Step 4, 0.05 g of the target product 3 was mixed with 1.0 g of polyethylene oxide, added to a round-bottom flask containing 25.0 mL of N,N'-dimethylformamide, with a solid content of 5%, heated at 60 ° C, and stirred for 2.5 h. Then, 0.4 g of succinonitrile and 0.3 g of lithium bis(trifluoromethanesulfonyl)imide (EO:Li=18:1) were added, and the mixture was heated and stirred at 65 ° C for 16 h to completely dissolve the mixture and mix it evenly. Finally, the above mixture was poured into a polytetrafluoroethylene plate and dried in a vacuum oven at 60 ° C for 48 h to obtain a composite solid electrolyte, which was recorded as PEOCCSN-5.
[0043] Example 3 Step 1, dissolve 1.65 g of chromium nitrate in 50 mL of distilled water, heat and stir at 30°C until dissolved, add 2.75 g of glucose to ensure sufficient carbon source, heat and stir at 30°C until completely dissolved. Then, place the solution in an oven to dry, set the temperature to 80°C, and dry for 8 h to obtain the target product 1; Step 2, weigh 0.75 g of product 1 and 2.35 g of carbon black, grind manually for 1 h. Then add an appropriate amount of isopropanol, use a ball mill for mechanical grinding, set the ratio of grinding ball mass to sample mass to 50:1, the rotation speed is 450 rpm, and the ball milling time is 8 h. After completion, dry in an oven for 5 h at 80 ° C to obtain the target product 2; Step 3: 0.5 g of the target product 2 was placed in a tube furnace for high-temperature carbonization, and argon was introduced as a protective gas at a flow rate of 40 mL min -1 The reaction temperature was 1400 °C and the heating rate was controlled at 10 °C min -1 The cooling rate is controlled at 3℃min -1 , the reaction time was 2 h. After the carbonization reaction was completed, the concentration was 0.1 mol L -1 After repeated rinsing with hydrochloric acid for 1-5 times, continue to use distilled water and anhydrous ethanol to repeat rinsing for 1-5 times. After completion, dry in an oven for 6 hours at a temperature of 80°C to obtain the target product 3; Step 4, 0.06 g of the target product 3 was mixed with 1.0 g of polyethylene oxide, added to a round-bottom flask containing 25.0 mL of N,N'-dimethylformamide, with a solid content of 6%, heated at 60 ° C, and stirred for 2.5 h. Then, 0.4 g of succinonitrile and 0.3 g of lithium bis(trifluoromethanesulfonyl)imide (EO:Li=18:1) were added, and the mixture was heated and stirred at 65 ° C for 16 h to completely dissolve the mixture and mix it evenly. Finally, the above mixture was poured into a polytetrafluoroethylene plate and dried in a vacuum oven at 60 ° C for 48 h to obtain a composite solid electrolyte, which was recorded as PEOCCSN-6.
[0044] In order to test the performance of the composite solid electrolyte prepared by the present invention, the following characterizations were performed, wherein: Figure 1 The XRD spectra of the composite solid electrolytes prepared in Examples 1 to 3 of the present invention show that Cr3C2 has four obvious characteristic peaks at 39.59°, 40.85°, 43.21°, 48.09° and 49.17°, which correspond to the diffraction peaks of (121), (230), (150), (060) and (310) crystal planes (JCPDS 35-0804). These intensities and positions confirm the successful preparation of Cr3C2. Pure polyethylene oxide (PEO) has two prominent peaks at 19.0° and 23.3°, while SN has a peak at 20.01° corresponding to carbon nitrogen (CN). The effect of the addition of fillers on the crystallinity of the composite solid electrolyte was further studied. With the increase of the content of Cr3C2 nanofiller, the intensity of the diffraction peak at 2θ=20.7° in the composite solid electrolyte gradually weakened. It is worth noting that when the addition amount of Cr3C2 reaches 6%, the diffraction peak intensity reaches the minimum value, indicating that the crystallinity of the film decreases under this specific composition. The specific crystallinity calculation results are shown in Table 1.
[0045] Table 1 Crystallinity of different composite solid electrolytes
[0046] Figure 2 The electrochemical window diagram (ESW) of the composite solid electrolyte prepared in Examples 1 to 3 of the present invention shows that, compared with inorganic solid electrolytes, PEO has better compatibility with lithium metal anodes, but its ESW (<3.9 V) is narrow and cannot be compared with high-voltage positive electrode materials. Therefore, current research on PEO-based electrolytes is mainly focused on improvement. The incorporation of Cr3C2 effectively inhibits the interaction between the -EO terminal groups in the polymer matrix and lithium metal, thereby extending the electrochemical stability window of the composite solid electrolyte to 4.97 V (vs. Li / Li after the introduction of Cr3C2. + ).
[0047] Figure 3 The electrochemical impedance spectra (a) of the composite solid electrolytes prepared in Examples 1 to 3 of the present invention at 25°C and the ionic conductivity (b) at different temperatures are shown. Ionic conductivity is an important parameter for evaluating composite solid electrolytes. At different temperatures, a series of composite solid electrolytes were assembled with steel plates (SS) into closed SS / / SS batteries for ESI testing. The ionic conductivity of the PEOCCSN-5 composite solid electrolyte was tested, and the results showed that it had a good ionic conductivity (σ) value of 3.81E-5 at room temperature. The analysis of the activation energy showed that the activation energy of the PEOCCSN-5 composite solid electrolyte was the lowest, at 0.51 eV. This can be attributed to the effective reduction of the crystallinity of the polymer matrix by adding fillers, thereby enhancing the mobility of the fragments and thus improving the conductivity of the ions. In addition, the nanomaterial has a larger effective interface, which enables it to establish an efficient ion transport network within the composite polymer electrolyte, thereby significantly improving the transmission rate of lithium ions. This enhancement is mainly due to the fact that the highly polar SN molecules promote the strong dissolution and self-diffusion / rotation of lithium ions, thereby accelerating the diffusion process of lithium ions. However, with the increase of inorganic filler content, the σ value of PEOCCSN-6 composite solid electrolyte decreased to 1.58E-5, mainly because the excess filler was easy to agglomerate, resulting in a decrease in the free volume in the polymer matrix, which led to a decrease in ionic conductivity. With the increase of temperature, the mobility of the polymer chain segments increased, resulting in an increase in ionic conductivity.
[0048] Example 4 A method for preparing a composite solid electrolyte using chromium carbide as filler comprises the following steps: Step 1, according to the mass fraction, 3 parts of chromium nitrate are dissolved in 50 parts of distilled water, heated and stirred at 25°C until dissolved, and then 5 parts of glucose are added to ensure sufficient carbon source, and heated and stirred at 25°C until completely dissolved. Then, the solution is placed in an oven to dry, the temperature is set to 60°C, and the drying time is 10 h to obtain the target product 1; Step 2, according to the mass fraction, the target product 1 and carbon black were mixed in a ratio of 1:5, and manually ground for 0.5 h. Then, an appropriate amount of isopropanol was added, and mechanical grinding was performed using a ball mill, and the ratio of the grinding ball mass to the sample mass was set to 50:1, the rotation speed was 400 rpm, and the ball milling time was 12 h. After completion, it was dried in an oven for 3 h at a temperature of 100 ° C to obtain the target product 2; Step 3: According to the mass fraction, 3 portions of the target product 2 were placed in a tube furnace for high-temperature carbonization, and argon was introduced as a protective gas at a flow rate of 10 mL min. -1 The reaction temperature was 1100°C and the heating rate was controlled at 5°C min -1 The cooling rate was controlled at 1℃ min-1 , the reaction time was 5 h. After the carbonization reaction was completed, the concentration was 0.1 mol L -1 After repeated rinsing with hydrochloric acid for 5 times, distilled water and anhydrous ethanol were used for repeated rinsing. After that, the mixture was dried in an oven for 3 h at 100 °C to obtain the target product 3; Step 4: Blend 1 part of the target product 3 with 25 parts of polyethylene oxide by weight, add to a round-bottom flask containing 25.0 mL of N,N'-dimethylformamide, heat at 50°C, and stir for 3 h. Then add succinonitrile and lithium bistrifluoromethanesulfonyl imide, wherein the ratio of succinonitrile to lithium bistrifluoromethanesulfonyl imide is 5:1 by weight, and the ratio of polyethylene oxide to lithium bistrifluoromethanesulfonyl imide is 16:1 by weight, continue heating and stirring for 10 h, dissolve the mixture completely, mix well, and finally pour the mixture into a polytetrafluoroethylene plate, dry it in a vacuum oven at 30°C for 48 h, and obtain a composite solid electrolyte.
[0049] Example 5 A method for preparing a composite solid electrolyte using chromium carbide as filler comprises the following steps: Step 1, according to the mass fraction, 3 parts of chromium nitrate are dissolved in 50 parts of distilled water, heated and stirred at 35°C until dissolved, 15 parts of glucose are added to ensure sufficient carbon source, and heated and stirred at 35°C until completely dissolved. Then, the solution is placed in an oven to dry, the temperature is set to 100°C, and the drying time is 6 hours to obtain the target product 1; Step 2, according to the mass fraction, the target product 1 and carbon black were mixed in a ratio of 3:5, and manually ground for 2 h. Then, an appropriate amount of isopropanol was added, and mechanical grinding was performed using a ball mill, and the ratio of the grinding ball mass to the sample mass was set to 100:1, the rotation speed was 600 rpm, and the ball milling time was 6 h. After completion, it was dried in an oven for 8 h at a temperature of 50 ° C to obtain the target product 2; Step 3: 8 parts of the target product 2 were placed in a tube furnace for high-temperature carbonization according to the mass fraction, and argon was introduced as a protective gas at a flow rate of 10 mL min -1 The reaction temperature was 1400 °C and the heating rate was controlled at 10 °C min -1 The cooling rate was controlled at 5℃ min -1 , the reaction time was 1 h. After the carbonization reaction was completed, the concentration was 0.5 mol L -1 After rinsing with hydrochloric acid for 5 times, continue to use distilled water and anhydrous ethanol to rinse for 5 times. After that, dry in an oven for 8 hours at a temperature of 50°C to obtain the target product 3; Step 4: Blend 1 part of the target product 3 with 20 parts of polyethylene oxide by weight, add to a round-bottom flask containing 50.0 mL of N,N'-dimethylformamide, heat at 80°C, and stir for 1 h. Then add succinonitrile and lithium bistrifluoromethanesulfonyl imide, wherein the ratio of succinonitrile to lithium bistrifluoromethanesulfonyl imide is 10:1 by weight, and the ratio of polyethylene oxide to lithium bistrifluoromethanesulfonyl imide is 18:1 by weight, continue heating and stirring for 16 h, dissolve the mixture completely, mix well, and finally pour the mixture into a polytetrafluoroethylene plate, dry it at 70°C in a vacuum oven for 24 h, and obtain a composite solid electrolyte.
[0050] Example 6 A method for preparing a composite solid electrolyte using chromium carbide as filler comprises the following steps: Step 1, according to the mass fraction, 3 parts of chromium nitrate are dissolved in 50 parts of distilled water, heated and stirred at 30°C until dissolved, and then 10 parts of glucose are added to ensure sufficient carbon source, and heated and stirred at 30°C until completely dissolved. Then, the solution is placed in an oven to dry, the temperature is set to 80°C, and the drying time is 8 hours to obtain the target product 1; Step 2, according to the mass fraction, the target product 1 and carbon black were mixed in a ratio of 2:5, and manually ground for 1 hour. Then, an appropriate amount of isopropanol was added, and mechanical grinding was performed using a ball mill, and the ratio of the grinding ball mass to the sample mass was set to 80:1, the rotation speed was 500 rpm, and the ball milling time was 10 hours. After completion, it was dried in an oven for 5 hours at a temperature of 80°C to obtain the target product 2; Step 3: According to the mass fraction, 5 parts of the target product 2 were placed in a tube furnace for high-temperature carbonization, and argon gas was introduced as a protective gas at a flow rate of 30 mL min. -1 The reaction temperature was 1300 °C and the heating rate was controlled at 8 °C min -1 The cooling rate was controlled at 2℃ min -1 , the reaction time was 2 h. After the carbonization reaction was completed, the concentration was 0.2 mol L -1 After rinsing with hydrochloric acid for 3 times, continue to use distilled water and anhydrous ethanol for 3 times. After that, dry in an oven for 5 h at 80 ° C to obtain the target product 3; Step 4: Blend 1 part of the target product 3 with 15 parts of polyethylene oxide by weight, add to a round-bottom flask containing 40 mL of N,N'-dimethylformamide, heat at 60°C, and stir for 2 h. Then add succinonitrile and lithium bis(trifluoromethanesulfonyl)imide, wherein the ratio of succinonitrile to lithium bis(trifluoromethanesulfonyl)imide by weight is 20:1, and the ratio of polyethylene oxide to lithium bis(trifluoromethanesulfonyl)imide by weight is 19:1. Continue heating and stirring for 14 h to completely dissolve the mixture and mix evenly. Finally, pour the above mixture into a polytetrafluoroethylene plate and dry it in a vacuum oven at 40°C for 30 h to obtain a composite solid electrolyte.
[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite solid electrolyte with chromium carbide as filler, characterized in that: The following steps are involved: S1: adding glucose to chromium nitrate solution, stirring and mixing, and drying to obtain mixture A; mixing mixture A with carbon black, grinding, adding isopropanol, ball milling, and drying to obtain mixture B; S2: Carburizing the mixture B under a nitrogen atmosphere to obtain chromium carbide; S3: Blending the chromium carbide with polyethylene oxide, adding them to N,N'-dimethylformamide, heating and stirring, then adding succinonitrile and lithium bis(trifluoromethanesulfonyl imide), continuing heating and stirring to completely dissolve the mixture, and mixing evenly, and after drying, obtaining the composite solid electrolyte with chromium carbide as filler.
2. The method for preparing a composite solid electrolyte with chromium carbide as filler according to claim 1, characterized in that: Calculated by mass, the ratio of glucose to chromium nitrate is 3:(5-15).
3. The method for preparing a composite solid electrolyte with chromium carbide as filler according to claim 1, characterized in that: In terms of mass fractions, the ratio of the mixture A to the carbon black is (1-3):
5.
4. The method for preparing a composite solid electrolyte with chromium carbide as filler according to claim 1, characterized in that: Mixture A and carbon black are mixed and ground, and isopropanol is added. During ball milling, the rotation speed is 400-600 rpm and the ball milling time is 6-12 h.
5. The method for preparing a composite solid electrolyte with chromium carbide as filler according to claim 1, characterized in that: In step S2, the carbonization process is specifically as follows: the heating rate is controlled to be 5-10°C min -1 , heat to 1100~1400℃, keep warm for 1~5 h, and control the cooling rate to 1~5℃ min -1 , to room temperature, completing the carbonization process.
6. The method for preparing a composite solid electrolyte with chromium carbide as filler according to claim 1, characterized in that: Calculated by weight, the ratio of the chromium carbide to the polyethylene oxide is (2-8):(8-12).
7. The method for preparing a composite solid electrolyte with chromium carbide as filler according to claim 1, characterized in that: In terms of mass fractions, the ratio of succinonitrile to lithium bis(trifluoromethanesulfonyl)imide is (10-50):
1.
8. The method for preparing a composite solid electrolyte with chromium carbide as filler according to claim 1, characterized in that: In step S3, after adding succinonitrile and lithium bis(trifluoromethanesulfonyl imide), heating and stirring are continued at a temperature of 50-80° C. for 10-16 h.
9. A composite solid electrolyte with chromium carbide as filler, characterized in that: The composite solid electrolyte with chromium carbide as filler has an ionic conductivity of 1*10 -6 ~1*10 -4 S cm -1 , the electrochemical window is 3.5V~5.5V.
10. A lithium metal battery, characterized in that: The composite solid electrolyte comprising chromium carbide as filler as claimed in claim 9.